2019
DOI: 10.1371/journal.pntd.0007612
|View full text |Cite
|
Sign up to set email alerts
|

An improved genome assembly of the fluke Schistosoma japonicum

Abstract: Background Schistosoma japonicum is a parasitic flatworm that causes human schistosomiasis, which is a significant cause of morbidity in China and the Philippines. A single draft genome was available for S . japonicum , yet this assembly is very fragmented and only covers 90% of the genome, which make it difficult to be applied as a reference in functional genome analysis and genes discovery. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 83 publications
2
56
0
1
Order By: Relevance
“…These authors used only two RNA-Seq libraries from S. japonicum, one from males and one from females [10]. Here we used a much higher number of RNA-Seq libraries from cercariae, sporocysts, schistosomula, and early-development or adult males and females, including the two libraries used by Liao et al [10], along with the newest version of the genome and transcriptome of S. japonicum, which were recently released with significant improvement in assembly contiguity [13]. Our group has recently developed an improved pipeline for identification of lncRNAs [12] and we showed that a large set of the S. mansoni transcripts that we previously annotated as lncRNAs with a different pipeline [14] and also that by Liao et al [10], now seem to represent partially processed pre-mRNAs arising from novel protein-coding genes annotated in the newest version of the S. mansoni genome and transcriptome [12].…”
Section: Thousands Of Lncrnas Are Expressed In S Japonicummentioning
confidence: 99%
See 2 more Smart Citations
“…These authors used only two RNA-Seq libraries from S. japonicum, one from males and one from females [10]. Here we used a much higher number of RNA-Seq libraries from cercariae, sporocysts, schistosomula, and early-development or adult males and females, including the two libraries used by Liao et al [10], along with the newest version of the genome and transcriptome of S. japonicum, which were recently released with significant improvement in assembly contiguity [13]. Our group has recently developed an improved pipeline for identification of lncRNAs [12] and we showed that a large set of the S. mansoni transcripts that we previously annotated as lncRNAs with a different pipeline [14] and also that by Liao et al [10], now seem to represent partially processed pre-mRNAs arising from novel protein-coding genes annotated in the newest version of the S. mansoni genome and transcriptome [12].…”
Section: Thousands Of Lncrnas Are Expressed In S Japonicummentioning
confidence: 99%
“…For this work, we used 66 S. japonicum RNA-Seq libraries that are publicly available at SRA from the following stages-cercariae, sporocysts, schistosomula, early-development, and adult males and females ( Supplementary File 10). The most recent SKCS01000000 version of the S. japonicum genome and transcriptome [13] were used as references.…”
Section: Transcriptome Assembly and Lncrnas Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the basic biology of schistosomes at the cellular and molecular levels is critical to identifying exploitable vulnerabilities of the parasite. High-throughput datasets, including high quality reference genomes for the three main species of schistosomes [5][6][7], have been generated. More recently, a thorough transcriptome analysis during the parasite's intra-mammalian development [8], and the identification of different cell types by single-cell RNA sequencing of various life cycle stages [9,10] represent significant steps towards deciphering cell fate and pathways involved in parasite development and host-parasite interactions.…”
Section: Introductionmentioning
confidence: 99%
“…All of the downstream analysis was based on clean reads with high quality. The improved genome of S. japonicum [30] was used as the reference genome. An index of the reference genome was constructed and paired-end clean reads were aligned to the S. japonicum reference genome using HISAT v2.1.0 [31].…”
Section: Bioinformatics Analysis Of Sequencing Datamentioning
confidence: 99%